Environmental Impact Assessment Discourse on Environmental Law Enforcement to Support Creative Tourism Industry: Overview from Indonesia and Spain - I Gusti Ayu Putri Kartika; Sri Winarsi; Rubén Martínez Dalmau; Bagus Hermanto (Universitas Negeri Semarang, 2024)
Activities in the creative tourism business can have a significant detrimental effect on the environment, including depletion of natural resources, pollution, and the physical impact of tourism. Environmental impact analysis, also known as EIA, and environmental law enforcement are critical to the creative tourism business. The EIA is a tool for preventing environmental pollution and/or damage, and enforcing environmental law is strongly tied to the apparatus's ability and citizens' compliance with applicable legislation, which covers three areas of law. The EIA is designed to keep environmental conditions at a certain level of quality to enable development continuity. EIA is one of the concrete tools for achieving and sustaining sustainable development. Since law enforcement is an attempt to ensure public order, as well as how crucial it is to comply with environmental law provisions to suppress the negative effects generated by environmental damage and pollution with the existence of tourism industry activities. This study is a normative legal study with applied statutory approach and conceptual approach. A literature review was undertaken to support the creative tourism industry, using primary and secondary legal documents in the form of legislation and legal literature that discuss EIA and environmental law enforcement.